Prehospital patients with acute isolated vertigo and imbalance referred for cerebral thrombolysis - De Schryver, S. R. H.; de Jonge, M.; van Luxemburg, R. P.; Geraedts, V. J.; De Schryver, E. L. L. M. (Frontiers in Neurology, 2025)
IntroductionPatients with acute vertigo and gait imbalance who are suspected of having a stroke, are increasingly referred to the hospital for intravenous thrombolysis treatment (IVT) with an increasing impact on the healthcare consumption. This study seeks to examine the medical feasibility of considering patients suffering from acute vertigo with imbalance in a prehospital setting without other neurological symptoms as potential candidates for IVT regarding its efficacy and impact on clinical outcomes.MethodsPatients referred for IVT with isolated vertigo as determined by the ambulance paramedics, were retrospectively enrolled from a single center. Patients were categorized by discharge diagnosis. Baseline characteristics were recorded. The Modified Rankin Score (mRS) was used to assess clinical outcomes.Results163 consecutive patients were included. Within this cohort, 5.5% were diagnosed with stroke, and 7.9% with suspected stroke. Among patients with (suspected) stroke, 59.1% received IVT. Among patients with (suspected) vestibular vertigo, 5.1% received IVT. Patients with (suspected) stroke exhibited higher National Institutes of Health Stroke Scale [NIHSS; Mdn 0 (Q1 0; Q3 1) and Mdn 2 (Q1 0; Q3 2.5)]. Additionally, walking ability did not significantly vary between patients with vestibular disease and stroke. The mRS scores after a 3-month period did not show significant differences between the groups.ConclusionAccurately differentiating between central and peripheral causes of vertigo in the hyperacute setting is challenging and carries the risk of overreferral and overtreatment. Combined with the lack of evidence that IVT improves clinical outcomes in patients with isolated vertigo and imbalance, and the increasing demand for healthcare, the authors suggest not referring these patients immediately for IVT but to consider adequate training of the paramedics in-field and other routes of medical assessment and treatment.